Role of Absorbable Polysaccharide Hemostatic Powder in the Prevention of Complications After Axillary Lymph Node Dissection in Breast Cancer Patients: A Multicenter Retrospective Analysis - Simona Parisi; Francesco Saverio Lucido; Francesca Fisone; Roberto Ruggiero; Salvatore Tolone; Francesco Iovino; Antonio Santoriello; Federico Maria Mongardini; Maddalena Paolicelli; Ludovico Docimo; Claudio Gambardella (Medicina)
Background and Objectives: Although breast surgery has undergone a drastic de-escalation in recent decades, axillary dissection is still indicated in some selected cases. Unfortunately, in 3–85% of cases, complications such as seroma formation occur, highlighting the need for more accurate hemostasis systems. The aim of this study is to evaluate the effectiveness of absorbable polysaccharide hemostatic such as HaemocerTM in preventing postoperative seroma. Materials and Methods: Patients referred to two surgery centers for a diagnosed breast cancer and candidates for axillary lymph node dissection were retrospectively evaluated and included in Group A (treated with HaemocerTM) and B (control group). The primary endpoints were the drain output after 48 h, the daily amount just before the removal, and the duration of axillary drainage placement. Secondary endpoints included the presence of seroma at the ultrasound (US) follow-up, significant blood loss, hematoma, the duration of surgery, and postsurgical complications. Results: The drain output within 48 h was 196 ± 93 vs. 286 ± 38 mL in Groups A and B, respectively (p = 0.013). The daily output before the removal was 40 ± 7 mL in Group A and 47 ± 2 mL in Group B (p = 0.049). The duration of axillary drainage placement was shorter in the experimental group (7 ± 3 days) compared to the control group (10 ± 1 days) with a statistically significant difference (0.037). During the US follow-up, on days 7, 15, and 30, the number of patients affected by seroma and the volumes were lower in the experimental group. Conclusions: The adsorbable hemostatic powder proved to be effective both in reducing the volume of drained fluid postoperatively and in decreasing the number and volume of reported seromas during the US follow-up.